Revealing Pre-service Teachers’ Reading Skills by Utilizing CEFR in their Self-assessment - Da Silva Lemos, Raquel; Elysa Hartati (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2021)
An English teacher should meet the standard English skills requirement since proficiency constitutes the foundation of non-native English teachers' professional confidence. This research aims to measure the pre-service teachers’ reading skills by using CEFR level and to investigate pre-service teachers’ awareness regarding their reading skills as their preparation as future English teachers. The study involved 40 (forty) students from the English program in a private University in Yogyakarta, and used Descriptive Mixed method to collect the data. The researcher used the questionnaire for the students' self-assessment, and the EF SET test to assess their reading skill level. The result of the questionnaire obtained shows 20% of students are in level A1, 25% are in level A2, 25% are in level B1, 12% are in level B2, 10% are in level C1, 8% are in the level C2). The test result shows 17% of the students are in level A1, 25% in level A2, 25% in level B1, 20% are in level B2, 8% are in level C1, and 5% are in the level C2. Six students joined the survey, of which 3 (three) rated themselves at a reading level above the result obtained on the test, and 3 (three) others rated themselves at a level lower than the result they got on the test. The result of this research showed that pre-service teachers should improve in English language proficiency and self-assessment. This knowledge expects to be used as information to those involved in the Educational field.